Impact of Gonadotrophin Releasing Hormone Antagonist Duration on In-Vitro Fertilization Outcome - Ozkan, Zehra Sema; Atılgan, Remzi; Kumbak, Banu; Sımsek, Mehmet; Sapmaz, Ekrem (Fırat University, 2013)
Objective: To evaluate whether oocyte quality, implantation and pregnancy rates in intra-cytoplasmic sperm injection (ICSI) cycles are related to the duration of gonadotrophin-releasing hormone antagonist (GnRH-ant) use. Material and Method: A total of 138 patients who were treated with GnRH-ant protocol at the IVF Clinic from March 2010 to January 2012 were enrolled in this study. The patients were classified into three groups according to duration of GnRH-ant use. Group 1: 4 days (n=51); group 2:5 days (n=57); group 3:6 days (n=30) antagonist application. Main outcome measures were implantation rate, pregnancy rate, fertilization rate, number of oocytes retrieved (NOR), number of mature oocytes (NMO). Results: The NOR and NMO were the lowest in group 1, intermediate in group 2, and the highest in group 3 respectively. There is no statistically significant difference between the groups in regard to total gonadotrophins used, fertilization, implantation or pregnancy rates. The pregnancy rates per ET and cycle were 37.9% and 31.8%, respectively. Conclusion: We noticed that longer GnRH-ant use was associated with more oocytes retrieved and more mature oocytes, but no difference in fertilization, implantation or pregnancy rates concluding that longer GnRH-ant use does not have a detrimental effect on in vitro fertilization outcome.

Amaç: Gonadotropin salgılatıcı hormon antagonisti (GnRH-ant) kullanım süresinin, in vitro fertilizasyon (IVF)/ intra-sitoplazmik sperm enjeksiyonu (ICSI) sikluslarında oosit kalitesi, implantasyon ve gebelik oranlarına etkisi olup olmadığını araştırmak. Gereç ve Yöntem: IVF kliniğimizde Mart 2010- Ocak 2012 tarihleri arasında GnRH-ant protokolü ile tedavi edilen 138 hasta çalışmaya dahil edildi. Hastalar GnRH-ant kullanım sürelerine göre 3 gruba ayrıldı. Grup 1: 4 gün (n=51); grup 2: 5 gün (n=57); grup 3: 6 gün (n=30). İmplantasyon, fertilizasyon ve gebelik oranları, toplanan oosit sayısı (TOS) ve matür oosit sayısı (MOS) bakılan ana parametrelerdir. Bulgular: Sonuçlara bakıldığında; TOS ve MOS grup1'de en düşük, grup 2'de orta ve grup 3'te en yüksek sayıda gözlendi. Gruplar arasında kullanılan toplam gonadotropin dozu, fertilizasyon oranı, implantasyon ve gebelik oranları açısından istatistiki anlamlı bir fark görülmedi. Siklus ve embriyo transferi başına görülen gebelik oranlarımız sırasıyla %31.8 ve %37.9 idi. Sonuç: Çalışmamızda GnRH-ant kullanım süresi uzadıkça toplanan oosit ve matür oosit sayısının arttığını, fakat fertilizasyon, implantasyon ve gebelik oranlarının fark etmemesi üzerinden, uzamış antagonist uygulamasının IVF sonucuna negatif etki oluşturmadığını gözlemledik.
Gonadotropin Salgılatıcı Hormon Antagonisti Uygulama Süresinin In-Vitro Fertilizasyon Sonuçlarına Etkisi